Review of Literature: Behind Helmet Blunt Trauma Mechanisms - Nsiampa, N.; Coghe, F. (Human factors and mechanical engineering for defense and safety, 2023)
Combat helmets are designed to protect military personnel during impact events by defeating incoming threats (blunt, ballistic, or blast threats) without inflicting serious or fatal injury to the head. Unlike the older generation of metallic helmets, the development of a new generation of helmets made of composite material types with high ballistic performance and low weight, such as UHMWPE, has improved the soldier’s ballistic protection and the ergonomic aspects of the helmets. However, one disadvantage of these light helmets is that they increase the back face deformation (BFD) of the helmet, increasing the risk of blunt trauma, also known as behind helmet blunt trauma (BHBT). BHBT is a type of non-penetrating ballistic injury caused by helmet shell BFD that can impair a soldier’s performance and even endanger his/her life. It is difficult to study BHBT mechanisms due to the highly dynamic nature and complex mechanisms involved during impacts. Closely related fields, such as the studies on non-lethal impacts, where there is more expertise, may provide additional insight for understanding BHBT, despite the fact that very few articles have investigated the link between these two fields. Due to a lack of understanding of BHBT, this article proposes a review of literature on the various mechanisms of blunt head injuries, particularly BHBT, in an effort to improve or design better protection systems to mitigate these injuries.